PENGARUH AUDIT FEE, PERENCANAAN AUDIT, DAN RISIKO AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BALI - Julianto, I Komang Agus; Yadnyana, I Ketut; Suputra, I.D.G Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
Some cases which involved public accounting firm  prove that few of them still did some violations and have lack audit quality of financial statements. Audit quality is a possibility that the auditor will find and report violations within the client's financial statement. Results of previous studies show that the audit fee, audit plan , and audit risk have an effect on audit quality (Arisinta, 2013) . Data collected method using quesionaire. The samples were 80 auditors were selected based on purposive sampling method. The samples were auditor who has at least two years of audit experience in public accounting firm in Bali with assumption that auditor already understand about the ethics in auditing and have a good capability of doing audit field.Data analysis technique used is multiple linear regression analysis. The results obtained are audit fee, audit plan , and audit risk have an positive effect on audit quality.
Keywords: Audit Quality, Audit Fee, Audit Plan, Audit Risk, Public Accounting Firm.